2021
DOI: 10.13057/biodiv/d220857
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove diversity and community structure of Mimika District, Papua, Indonesia

Abstract: Abstract. Setyadi G, Pribadi R, Wijayanti DP, Sugianto DN. 2021. Mangrove diversity and community structure of Mimika District, Papua, Indonesia. Biodiversitas 22: 3562-3571. Despite being one the largest mangrove forest in the world, there are few studies on mangrove diversity and community structure in Mimika, Papua Province. The study collected data from 4 estuaries of Mimika Region, i.e. Kamora, Tipuka, Ajkwa and Minajerwi. Mangrove species, tree diameter at breast height and canopy height data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
0
14
0
4
Order By: Relevance
“…These heights are comparable with mangroves found in most areas in Indonesia, such as Bali [51], Porong Delta, East Java [52], Mahakam Delta [25], etc. But they are too short compared to the mangrove height in Papua, which can reach more than 40 m high, e.g., [25,53,54].…”
Section: Canopy Height and Lorey's Heightmentioning
confidence: 99%
“…These heights are comparable with mangroves found in most areas in Indonesia, such as Bali [51], Porong Delta, East Java [52], Mahakam Delta [25], etc. But they are too short compared to the mangrove height in Papua, which can reach more than 40 m high, e.g., [25,53,54].…”
Section: Canopy Height and Lorey's Heightmentioning
confidence: 99%
“…Other studies on the coasts of major cities, namely Jakarta Bay and Muara Kapuk, have identified 5 to 9 mangrove species (Rumondang et al 2021;Sari et al 2019). The number of mangrove species found in remote areas with natural mangrove forests is considerably higher, as evidenced by studies in Mimika Papua (66 species), Segara Anakan Cilacap, Central Java (16 species) and Kutai National Park, East Kalimantan (17 species) (Poedjirahajoe et al 2019;Setyadi et al 2021;Widyastuti et al 2018). Excellent water and sediment quality, low environmental pollution, and the absence of illegal logging are all factors that contribute to the optimal growth of mangrove forests in remote coastal areas.…”
Section: Mangrove Community Structurementioning
confidence: 97%
“…Bentuk adaptasi yang ditunjukkan oleh vegetasi mangrove antara lain adalah sistem perakaran yang kuat, memiliki akar nafas (pneumatofora) dan struktur daun yang mampu bertahan terhadap kadar garam yang tinggi. Beberapa genus vegetasi mangrove yang dapat ditemukan di Indonesia antara lain Avicennia, Sonneratia, Rhizophora, Bruguiera, Ceriops, Xylocarpus, Lummitzera, Aegiceras, Excoecaria, Aegiceras, Scyphyphora dan Nypa (Setyadi et al, 2021;Theresia et al, 2016).…”
Section: Pendahuluanunclassified
“…Secara umum perhitungan MHI dikembangkan untuk menilai kesehatan mangrove pada tingkat ekosistem berdasarkan 3 parameter utama struktur tegakan mangrove yaitu diameter batang, tutupan tajuk dan kepadatan. Nilai MHI dapat ditentukan melalui pengambilan data lapang (Schaduw et al, 2021;Setyadi et al, 2021) maupun memanfaatkan citra satelit. Beberapa penelitian yang memanfaatkan citra satelit untuk menentukan MHI berdasarkan nilai NDVI antara lain dilakukan oleh Akbar et al (2020), Maulidiyah et al (2017) serta Sukojo & Arindi (2019).…”
Section: Pendahuluanunclassified